2014
DOI: 10.1080/00268976.2013.871365
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic analysis of the interaction of partially hydrophobic cationic polyelectrolytes with sodium halide salts in water

Abstract: Isothermal titration calorimetry was used to determine the temperature and concentration dependence of the enthalpy of mixing of 3,3-and 6,6-ionene fluorides, bromides, and iodides with low molecular weight salts (NaF, NaCl, NaBr, and NaI) in water. The magnitudes of the enthalpies, measured in the temperature range from 273 to 318 K, depended on the number of methylene groups on the ionene polyion (hydrophobicity), and on the anion of the added salt (ion-specificity). All enthalpies of mixing of 3,3-and 6,6-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…23 temperatures and using this information obtained the excess Gibbs free energy, enthalpy, and entropy contributions for displacement of fluoride ions in the mixing process with NaBr, NaCl, and NaI salts at T = 298 K. The results for 3, 3-ionenes, shown in Table I of that paper, indicated that excess free energy function decreases in order from F − toward I − . The same holds true for the relevant enthalpy and entropy terms.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…23 temperatures and using this information obtained the excess Gibbs free energy, enthalpy, and entropy contributions for displacement of fluoride ions in the mixing process with NaBr, NaCl, and NaI salts at T = 298 K. The results for 3, 3-ionenes, shown in Table I of that paper, indicated that excess free energy function decreases in order from F − toward I − . The same holds true for the relevant enthalpy and entropy terms.…”
Section: Discussionmentioning
confidence: 89%
“…ii) Experimental 22,23 and MD simulation data concerning the strength of counter-ion binding to the ionene oligoion arrive at the following sequence for the halide ions: F − (weakest binding) < Cl − < Br − < I − (strongest binding). [26][27][28][29] The situation recently encountered with the hydrophobic 12, 12-ionenes seems to differ from the above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations